Curriculum Organization Development Process in Developing Education Indonesia - Abdul Halim (CV. ADIBA AISHA AMIRA, 2022)
Learning that takes place in the classroom without a clear curriculum will make it difficult for students to understand the lessons delivered by the teacher. Organizing the curriculum means choosing clear and objective goals that are in accordance with the needs and interests of students. The elements of the curriculum organization include: concepts, generalizations, skills, values. The curriculum organization model is a subject approach, combined subjects, broad coverage, integrated curriculum, core curriculum, activity curriculum